THE IMPACT OF MULTIMEDIA DEVICES AND ROLE-PLAY IN IMPROVING STUDENTS’ ENGLISH-SPEAKING SKILLS - Jusni (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2025)
This study investigates the impact of multimedia-supported role-play on students’ English-speaking skills through a mixed-methods approach employing a pre-test–post-test control group design. A total of 80 secondary school students participated in the study, consisting of 40 students in the experimental group and 40 students in the control group. Speaking proficiency was measured using a 60-item multiple-choice speaking skills test assessing five components: pronunciation, fluency, vocabulary, grammar, and comprehension. Quantitative data were analysed using descriptive statistics, paired-sample t-tests, and independent-sample t-tests, while qualitative insights were obtained through semi-structured interviews. The results reveal that both groups started at comparable proficiency levels, predominantly within the “moderate” and “fairly good” categories. However, after eight weeks of instruction, the experimental group demonstrated statistically significant improvement across all speaking components (p < .001), with mean gains ranging from 24.85 to 28.05 points and performance levels shifting to “very good” and “excellent.” In contrast, the control group showed only minimal improvement, with mean gains between 4.50 and 5.80 points, remaining within the “moderate” category. Independent t-test results confirmed significant post-test differences in favour of the experimental group across all speaking components. Qualitative findings further supported the quantitative results, indicating that multimedia input enhanced pronunciation accuracy and vocabulary acquisition, while role-play activities reduced anxiety, increased speaking confidence, and promoted active oral participation. The study concludes that multimedia-supported role-play is a highly effective pedagogical strategy for developing students’ English-speaking skills and is strongly recommended for integration into EFL classroom instruction.